2015
DOI: 10.1186/2193-1801-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Women with large (≥3 cm) and locally advanced breast cancers (T3, 4, N1, 2, M0) receiving neoadjuvant chemotherapy (NAC: cyclophosphamide, doxorubicin, docetaxel): addition of capecitabine improves 4-year disease-free survival

Abstract: PurposeTo determine whether capecitabine (X), combined with docetaxel (T) following doxorubicin (A) and cyclophosphamide (C), enhanced the pathological complete response (pCR) in the breast and axillary lymph nodes (ALNs) of women with large or locally advanced breast cancers (LLABCs) improving outcome, and the effect on quality of life (QoL).Patients and methods117 women were enrolled, 112 randomised to 2 cycles of AC (60 mg/m2, 600 mg/m2) given 3 weekly. Tumour responses were assessed by magnetic resonance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…A pCR following NAC in breast cancer has been shown in some studies to be a surrogate marker for a good prognosis and survival [ 46 , 66 ]. Cortazar et al described a correlation between favourable outcome and pCR in breast cancer [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A pCR following NAC in breast cancer has been shown in some studies to be a surrogate marker for a good prognosis and survival [ 46 , 66 ]. Cortazar et al described a correlation between favourable outcome and pCR in breast cancer [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was a significant association between TIMs and tumour ER status and grade and between pCR and tumour ER status and grade. Highly proliferative, triple-negative breast cancers are significantly associated with high rates of pCR but have a poor DFS and OS [ 9 , 46 , 68 ]. Esserman et al showed by studying breast cancer subsets that a pCR was a better predictor for a DFS [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We carried out an immunohistochemical analysis of various lymphocytic immune cells and humoral factors infiltrating LLABCs. We documented the pathological impact of NAC on the tumour microenvironment and the possible contribution of different host immune cells and humoral factors to an immune-mediated tumour cell death and pCR to NAC, a recognised surrogate marker of a beneficial long-term clinical response in breast cancer [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%